Formulation of structured bounding surface model with a destructuration law for natural soft clay - Yunliang Cui; Xinquan Wang; Shiming Zhang (Functional Materials, 2017)
A destructuration law considering both isotropic destructuration and frictional destructuration was suggested to simulate the loss of structure of natural soft clay during plastic straining. The term isotropic destructuration was used to address the reduction of the bounding surface, and frictional destructuration addresses the decrease of the critical state stress ratio as a reflection of reduction of internal friction angle. A structured bounding surface model was formulated by incorporating the proposed destructuration law into the framework of bounding surface constitutive model theory. The proposed model was validated on Osaka clay through undrained triaxial compression test and one-dimensional compression test. The influences of model parameters and bounding surface on the performance of the proposed model were also investigated. It is proved by the good agreement between predictions and experiments that the proposed model can well capture the structured behaviors of natural soft clay.